2002
DOI: 10.1089/10928750260418926
|View full text |Cite
|
Sign up to set email alerts
|

Field-Scale Bioremediation of Soil Contaminated with Crude Oil

Abstract: Field-scale remediation of oil-contaminated soils from the Liaohe Oil Fields in China was examined using composting biopiles in windrow technology. Micronutrient-enriched chicken excrement and rice husk were applied as nutrition and a bulking agent. The lipase activities of indigenous micro-organisms were analyzed, and three indigenous fungi with high lipase activities was identified. An inoculum consisting of the three indigenous fungi and one introduced (exotic) fungus was applied to four different types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…In some cases, the population of introduced strains may remain stable even after one year (Mishra et al, 2001). However, researchers reported that the introduction of exotic microorganisms did not improve the remediation and that the inoculation of oil-contaminated sites with nonindigenous species is likely to fail (Li et al, 2002;Thomassin-Lacroix et al, 2002;Cavalca et al, 2002). It is suggested that the effect and efficiency of inoculated microorganism depend on the environmental conditions such as the existence of indigenous microorganisms, nutrient level and amount of inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, the population of introduced strains may remain stable even after one year (Mishra et al, 2001). However, researchers reported that the introduction of exotic microorganisms did not improve the remediation and that the inoculation of oil-contaminated sites with nonindigenous species is likely to fail (Li et al, 2002;Thomassin-Lacroix et al, 2002;Cavalca et al, 2002). It is suggested that the effect and efficiency of inoculated microorganism depend on the environmental conditions such as the existence of indigenous microorganisms, nutrient level and amount of inoculation.…”
Section: Discussionmentioning
confidence: 99%
“…This is a short-term technology and may last from a few weeks to a few months (FRTR, 1999l). Biopiles are similar to landfarming but in the latter the soil is aerated through tilling or plowing (USEPA, 1998e;Jorgensen et al, 2000;Filler et al, 2001;Li et al, 2002).…”
Section: Biopilesmentioning
confidence: 99%
“…Therefore, the successful treatment of a contaminated site depends on proper selection, design, and adjustment of the remediation technology's operations based on the properties of the contaminants and soils and on the performance of the system. Detailed descriptions of individual technologies can be found in Chareneau et al (1995), API (1993), Alexander (1994), Demars et al (1995), and Anderson (1995), USEPA reports (USEPA, 1995(USEPA, -1998, Federal Remediation Technologies Roundtable reports (FRTR, 1999a -q), Reddy et al (1999), RAAG (2000), Feng et al (2001), Hejazi (2002), Kao et al (2001), Li et al (2002), Abbott et al (2002), Guerin et al (2002), Barnes (2003), Chu (2003), Halmemies et al (2003), Khan and Husain (2003), Juhasz et al (2003), Liang et al (2003), Wilk (2003) and Wait and Thomas (2003).…”
Section: Introductionmentioning
confidence: 99%
“…Another reason why natural attenuation has failed is the presence of silty clay or pure clay soil in some areas. Natural attenuation does not work well in fine grained soils [34][35][36][37][38][39][40].…”
Section: Methodology (Decision Support System)mentioning
confidence: 99%